Effect of simulated emergency skills training and assessments on the competence and confidence of medical students - I Treadwell (South African Medical Association, 2015)
Background. At Medunsa, Pretoria, South Africa, the training of final-year medical students includes the management of simulations that incorporate, inter alia, the following emergency skills: cardiopulmonary resuscitation (CPR), defibrillation, airway suctioning, oropharyngeal airway placement, endotracheal intubation and bag-valve-mask ventilation. Other than CPR, all emergency training of the 2012 student group was by means of apprenticeship in clinical rotations. Therefore, there was no evidence of the students’ competence or confidence with regard to their performance of emergency skills. Objectives. To explore the effect of simulated skills training and assessments on medical students’ competence and confidence when using the skills required to manage clinical emergencies. Method. A one-group pretest post-test quasi-experimental design was used, with a convenience sample (n=82) comprising final-year medical students from 3 of the 6 annual Family Medicine rotations. The participants’ competence (knowledge and selected emergency skills as per curriculum) and confidence were assessed before training. The intervention comprised training in relevant theory, demonstrations and supervised hands-on practice. The post-training assessments were a repeat of the pretraining assessments. Results. The improvement in participants’ confidence and competence levels when performing all the emergency skills on completion of the demonstrations and hands-on practice was highly significant (p≤0.001). Participants were unanimous in their opinion that pre-assessments had enhanced their learning experience. Conclusions. The strategy of teaching/learning and assessment of emergency skills in simulation was highly effective in enhancing the competence and confidence of medical students when managing a clinical emergency. However, students appeared to be overconfident, which could be ascribed to ignorance, and possibly indicates that feedback during training should be improved.